Buyer satisfaction and loyalty - evidence from the industrial goods market - Hishamuddin Ismail,; Zaharah Bakar,; Aliah Hanim M. Salleh, (Penerbit Universiti Kebangsaan Malaysia, 2006)
What makes organizational buyers of products satisfied? To what extent does customer satisfaction imply customer loyalty in the industrial goods market? Past research have shown the dire need for marketers to seek and manage the right ingredients of customer satisfaction as a vital means of building customer loyalty. Past satisfaction-loyalty studies were predominantly in the consumer goods and services contexts. This study aims to fill the dearth in research in the industrial goods context. By using evidence from a sample of buyers of one supplier of semiconductor products in the industrial goods market, this study seeks to further understand the dynamics of this complex satisfaction-loyalty relationship. The best predictor of buyer satisfaction in this industrial market is found to be cost of ownership, while other determinants - service quality, product quality and delivery aspects are found to be positively linked with overall buyer satisfaction. Suggestions for future research aTe also given to address the present study s limitations.